Experimental Investigation of MgAl-NO2 and MgAl-CO3 LDHs on Durability of Mortar and Concrete - Zhanguo Li; Huan Du; Zigeng Wang; Caiyun Jin; Yue Li (Advances in Materials Science and Engineering)
Two kinds of layered double hydroxides (LDHs), MgAl-NO2 (N-LDH) and MgAl-CO3 (C-LDH), were incorporated to study the durability of mortar and concrete. The LDH contents of mortar were 1%, 2%, and 4% by mass and the LDH contents of concrete were 0.5%, 1%, 2%, 4%, respectively. The effect of LDHs on sulfate resistance of mortar was studied through dry-wetting cycle test, compressive strength test, and flexural strength test. In addition, the effects of LDHs on pore structure, chloride resistance, carbonation resistance, shrinkage, and creep of concrete were investigated by SEM, mercury injection test, XRD, chloride ion diffusion coefficient test, chloride salt corrosion depth test, carbonation depth test, shrinkage test, and creep test. The results showed that LDHs can improve the ability of resisting ion corrosion, carbonization, shrinkage, and creep, reduce the pore content, and optimize the pore structure of mortar and concrete to some extent. Moreover, 4% LDHs had a better effect on improving the durability of mortar and concrete compared to 0.5%, 1%, and 2% LDHs, and the effect of C-LDH was better than N-LDH.